(untitled) (Herald of Journalism, 2018)
In the article author deals with issues of today lighting in the media policy of the President of Kazakhstan Nursultan Nasarbayev for the development of the relationship of state and society. Key words: president, journalist, information, economic analysis, newspaper, rubric, information society, globalization, democracy, policy, independent state.